Assessment of Sustainable Elimination Criteria for Iodine Deficiency Disorders Recommended by International Organizations - Fan, Lijun; Meng, Fangang; Sun, Qihao; Zhai, Yuqian; Liu, Peng (Frontiers in Nutrition, 2022)
Enormous efforts have been made to evaluate the worldwide prevention and control of iodine deficiency disorders (IDD). This study evaluated China’s achievements in IDD prevention and control against WHO criteria for sustainable elimination of IDD. The study sample consisted of 556,390 school-aged children and 271,935 pregnant women enrolled in the 2018 China National IDD Surveillance. As a result, at the national level, median urine iodine concentration (MUIC) was 206.1 µg/L and 163.5 µg/L in children and in pregnant women, respectively. The proportion of households consuming adequate iodized salt (PHCAIS) was 90.2%. The prevalence rates of goiter in children and thyroid disease in pregnant women were 2.0% and 0.8%, respectively. MUIC showed significant nonlinear increasing trends with increasing PHCAIS in both children and pregnant women. The prevalence of thyroid disease in pregnant women had a sharp decreasing trend with increasing PHCAIS. Of note, the prevalence rate of goitre in children and thyroid disease in pregnant women against MUIC both presented as significant U-shaped curves, with the lowest prevalence at 100-300ug/L of MUIC in children and 150-250 μg/L in pregnant women. PHCAIS, MUIC and the programmatic indicators at the national level were all above their cut-offs proposed in the 2007 Criteria. Evaluation by adding the prevalence of goiter (<5%) yielded the different results at the county level. Sustainable elimination of IDD has been achieved nationally. 2018 Chinese surveillance data support expansion of global cut-offs for optimal iodine status in school age children from 100-199 μg/L to 100-299 μg/L as recommended by others and the lower limit of MUIC (150 μg/L) in pregnant women also seems justified. Inclusion of goitre prevalence <5% in our analysis reduced the number of municipalities and counties which had achieved sustainable elimination of IDD.